Nomograms for Calculation of Oxygen Consumption and Respiratory Exchange Ratio - Nunn, J. F. (1972)
Nomograms have been prepared whereby the respiratory exchange ratio may be derived from the concentrations of carbon dioxide and oxygen in expired gas and oxygen consumption from the volume and oxygen concentration of expired gas; they apply only to patients breathing room air. The nomogram for the respiratory exchange ratio has an error of less than 0·01, which is the limit of visual discrimination on the nomogram. The nomogram for oxygen consumption has an error of standard deviation 7·73 ml/min. This error may be substantially reduced by excluding cases with a respiratory exchange ratio outside the range 0·70-0·93. Under these conditions the maximum error was 10 ml/min, which is acceptable for a wide range of clinical purposes.